Trends in oncology drug lags in Japan from 2001 to 2020: A cross‐sectional study - Hideki Maeda; Asuka Hara; Momoka Ofuchi; Riko Shingai; Toshihiro Misumi; Yuna Murai (Wiley, 2023)
Abstract Anticancer drugs are essential in the treatment of serious diseases, but their applications are limited by drug lags. This study investigated the characteristics of anticancer drugs approved in Japan over the past 20 years and compared the drug lag trends between Japan and the US. We assessed the changes in drug lag between Japan and the US and the factors affecting the drug lags using publicly available data for anticancer drugs approved in Japan from January 2001 to December 2020. A total of 299 anticancer drugs were approved in Japan in the last 20 years. The approval lag median between the US and Japan was 498 days (16.6 months), peaking in 2002, and decreasing annually thereafter. The minimum approval lag was 173.5 days (5.7 months) in 2018. Multivariate regression analysis revealed that "global simultaneous strategy," "catch‐up strategy," and "immunotherapy" are major factors shortening the drug lag. In the past decade, 226 anticancer drugs were approved in Japan. The drug lag for anticancer drugs between Japan and the US peaked in 2002, after which it declined sharply to less than a year. However, the lag was shortest in 2018.